Youth Politician School Yogyakarta Satunama Foundation as a Political Education and Democracy Effort for Youth - Zulfah Lis Syafawati; Suharno Suharno (Universitas Islam Negeri Raden Fatah Palembang, 2024)
This study aims to determine the implementation of the Young Politician School by the Yogyakarta SATUNAMA Foundation as an effort to educate political and democratic youth. This research uses this type of qualitative research with a descriptive approach. Data collection techniques using interviews and documentation. Data analysis was carried out using the model of Miles et al consists of (1) data collection, (2) data condensation, (3) data display, and (3) drawing conclusions/verification. The results showed that the Yogyakarta SATUNAMA Foundation established the Young Politician School to address the low political participation of youth and the declining quality of democracy in Indonesia. The contribution of the SATUNAMA Foundation in developing democracy in Indonesia by focusing on young political actors to have political literacy skills through the Young Politician School to analyze the political environment is a challenge and opportunity for young politicians in developing a democratic political culture. The Young Politician School is implemented with 3 different levels, namely level I, II, and III by covering the competence of knowledge, character.